T152. AZERI RECENT ONSET ACUTE PHASE PSYCHOSIS SURVEY (ARAS COHORT): PRELIMINARY REPORTS FROM AN OBSERVATIONAL COHORT OF FIRST EPISODE PSYCHOSIS IN IRAN. (18th May 2020) - Farhang, Sara; Ghaemmaghami, Mehrdad; Noorazar, Gholamreza; Veling, Wim; Malek, Ayyoub; Shafiee-Kandjani, Ali Reza; Alizadeh, Behrooz Z; Bruggeman, Richard
Abstract: Background: Azeri Acute phase/Recent onset psychosis Survey (ARAS) is the first from central Asia to study the course of patients with recent onset psychosis. The aim is to reveal indicators for understanding the risk and resilience factors, and for choosing the best personalized treatment strategy. Methods: The catchment area is north-west of Iran, with the majority having an Azeri ethnic background. All participants are evaluated for clinical signs and symptoms as well as risk and resilient factors and followed up for outcome in several domains. Here we give report of first 100 registered patients (male/female: 1.6). Results: Patients are diagnosed with schizophrenia (23), brief psychotic disorder (4), schizophrenifom (9), amphetamine induced psychotic disorder (12), psychotic disorder NOS and schizoaffective (27). The mean score of PANSS was 26.79±20.62. Their mean age is 29.8±11.5. High school diploma or higher was achieved by 45. While 60 were single, 21 were married at the moment and 35 had children. All of patients were Muslims, 30 scored moderate on religiosity and the remaining scored high. Level of multidimensional perceived social support was moderate and high in 80 patients. Only 4 were living alone. Level of internalized stigma was moderate and high in 16 patients. Metabolic syndrome was diagnosed in 11. Almost one third of patients had ever used substance including cigarette (20), alcohol (12), opioids (5), amphetamine (15) and cannabis (5). The most prevalent prescribed medication is risperidone (78). Metabolic syndrome criteria were fulfilled in 16 patients. Discussion: Preliminary reports from ARAS cohort shows few differences between Iranian and European patients. Lower rate of metabolic syndrome, substance use (especially cannabis) and higher rate of religiosity, having social support, married situation and having children are noticed.